PENDAMPINGAN DAN EVALUASI KETERSEDIAAN AIR IRIGASI WILAYAH KELOMPOK TANI RAHARJO DESA GUMUKMAS, KECAMATAN GUMUKMAS, KABUPATEN JEMBER - Pambudi, Akbar Setyo; Andriyani, Idah; Hita, Muhammad Arga; Karomah Hidayah, Darul Alfan; Abiyyu, Ahmad Naufal; Arif, Ahmad Zidan; Jones, Mochammad Roy (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2025)
Irrigation is an effort to provide water, manage water (management), and drainage for plant needs. Raharjo Farmers Group is one of the farmer groups in Gumukmas Village, Gumukmas District, Jember Regency, which is located close to the coastal area or can be said to be the most downstream area of ​​the flow. This research activity entitled "Assistance and Evaluation of Irrigation Water Availability in the Raharjo Farmers Group Area, Gumukmas Village, Gumukmas District, Jember Regency, was carried out with the aim of obtaining data and information related to water sources that irrigate agricultural land which are used as the basis for processing recommendation maps for assistance and evaluation of irrigation water availability. The first stage of this activity is carried out with direct survey and investigation activities in the field, at this stage existing field conditions will be obtained in the form of channel conditions, building conditions (if any), information on the Cropping Index, Cropping Patterns and so on. After the survey and investigation stages, the design planning stage continues, at this stage the data that has been collected will continue to the data processing stage according to the needs of the research activity. The final planned result is a thematic map containing information on points or recommendation points or channel problems. The thematic map is used as study material for the East Java Provincial Agriculture and Food Security Service as a reference for policy making for better development.